Chemotherapy-induced peripheral neuropathy in children and adolescent cancer patients - Tay, Nicolette; Laakso, E-Liisa; Schweitzer, Daniel; Endersby, Raelene; Vetter, Irina; Starobova, Hana (Frontiers in Molecular Biosciences, 2022)
Brain cancer and leukemia are the most common cancers diagnosed in the pediatric population and are often treated with lifesaving chemotherapy. However, chemotherapy causes severe adverse effects and chemotherapy-induced peripheral neuropathy (CIPN) is a major dose-limiting and debilitating side effect. CIPN can greatly impair quality of life and increases morbidity of pediatric patients with cancer, with the accompanying symptoms frequently remaining underdiagnosed. Little is known about the incidence of CIPN, its impact on the pediatric population, and the underlying pathophysiological mechanisms, as most existing information stems from studies in animal models or adult cancer patients. Herein, we aim to provide an understanding of CIPN in the pediatric population and focus on the 6 main substance groups that frequently cause CIPN, namely the vinca alkaloids (vincristine), platinum-based antineoplastics (cisplatin, carboplatin and oxaliplatin), taxane (paclitaxel and docetaxel), epothilones (ixabepilone), proteasome inhibitors (bortezomib) and immunomodulatory drugs (thalidomide). We discuss the clinical manifestations, assessments and diagnostic tools, as well as risk factors, pathophysiological processes and current pharmacological and non-pharmacological approaches for the prevention and treatment of CIPN.